Institutional Quality, Foreign Direct Investment, and Regional Integration: Empirical Evidence From CEN-SAD. (January 2023) - Kwaw-Nimeson, Enoch; Tian, Ze
This study investigates the institutional quality effects on the foreign direct investment (FDI)–regional integration nexus in the Community of Sahel-Saharan States (CEN-SAD). The novelty of our approach extends the regional integration theory in Africa by employing the Africa Regional Integration Index (ARII) and utilizes a dynamic panel data model based on the one-step system generalized method of moments (SYS-GMM) estimation to explore the institutional quality effects on the relationship between FDI location advantages and inflows and dimensions of regional integration. Our study highlights macroeconomic integration as the strongest indicator of regional integration as well as the most crucial determinant of FDI in CEN-SAD. We also discovered that FDI inflows into the lower-middle income countries (LMICs) were only slightly higher than in low-income countries (LICs). Our results infer that institutional reforms augment FDI location advantages and enhance FDI inflows irrespective of the level of integration in the Community.